Model Kepemimpinan Dalam Pelaksanaan Reformasi Birokrasi Di Kabupaten Jember - * Syafi'i (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2012)
This research is based failure of leadership in Jember district in the implementation of bureaucratic reform. Therefore, this study investigates what factors are the cause of this failure and then try to build models of effective leadership in implementing the reform of the bureaucracy. The research method is qualitative method. This study found a massive, that there is a strong will that leadership in Jember district to implement reform of the bureaucracy can be seen from the product and declaring local regulations regarding institutional strengthening, empowering the communities - poverty alleviation, and public service. However, in the implementation of a failure, seen enough and 72% of civil servants are not happy over and over 90% of the people enough and less satisfied with the leadership in the district of Jember. Failure of leadership in implementing bureaucratic reform in Jember district was not caused by a factor of capability, quality leadership. However, this failure is more influenced by the dependence of political economy a top leader at the district level because the process of recruitment and leadership system characterized by high political and economic costs. A leader is not autonomous in policy making and implementation, because funders and parties involved in it. A theoretical model of leadership that is able to effectively implementationÂ the reform of the bureaucracy and would be a public service-based leadership. Public service-based leadership was marked by visionary character, ideals, social skills, multicultural intelligence, spiritual intelligence, participatory and democratic. But the quality of leadership at the top would be redundant if the political process is still characterized by high economic cost of the election which created the political economic dependence. For the case of failure of Jember district leadership in implementing bureaucratic reform influenced the high economic costs in the political process. Therefore there should be regulations governing the elections cheap, do political education to the community, public control, and law enforcement.Keywords: Leadership, bureaucratic reform, high cost economic, Jember district.